Outpatient Tinnitus Clinic, Self-Help Web Platform, or Mobile Application to Recruit Tinnitus Study Samples? - Probst, Thomas; Pryss, Rüdiger C.; Langguth, Berthold; Spiliopoulou, Myra; Landgrebe, Michael; Vesala, Markku; Harrison, Stephen; Schobel, Johannes; Reichert, Manfred; Stach, Michael; Schlee, Winfried (Frontiers in Aging Neuroscience, 2017)
For understanding the heterogeneity of tinnitus, large samples are required. However, investigations on how samples recruited by different methods differ from each other are lacking. In the present study, three large samples each recruited by different means were compared: N=5017 individuals registered at a self-help web platform for tinnitus (crowdsourcing platform Tinnitus Talk), N=867 users of a smart mobile application for tinnitus (crowdsensing platform TrackYourTinnitus), and N=3786 patients contacting an outpatient tinnitus clinic (Tinnitus Center of University Hospital Regensburg). The three samples were compared regarding age, gender, and duration of tinnitus (month or years perceiving tinnitus; subjective report) using chi-squared tests. The three samples significantly differed from each other in age, gender, and tinnitus duration (p<.05). Users of the TrackYourTinnitus crowdsensing platform were younger, users of the Tinnitus Talk crowdsourcing platform had more often female gender, and users of both newer technologies (crowdsourcing and crowdsensing) had more frequently acute/subacute tinnitus (<3 months and 4-6 months) as well as a very long tinnitus duration (>20 years). Implications of these findings for clinical research are that newer technologies such as crowdsourcing and crowdsensing platforms offer the possibility to reach individuals hard to get in contact with at an outpatient tinnitus clinic. Depending on the aims and the inclusion / exclusion criteria of a given study, different recruiting strategies (clinic and / or newer technologies) offer different advantages and disadvantages. In general, study results might be increased when tinnitus study samples are recruited in the clinic as well as via crowdsourcing and crowdsensing.